2004
DOI: 10.1172/jci22353
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure: definitions, diagnosis, pathogenesis, and therapy

Abstract: Acute renal failure (ARF), characterized by sudden loss of the ability of the kidneys to excrete wastes, concentrate urine, conserve electrolytes, and maintain fluid balance, is a frequent clinical problem, particularly in the intensive care unit, where it is associated with a mortality of between 50% and 80%. In this review, the epidemiology and pathophysiology of ARF are discussed, including the vascular, tubular, and inflammatory perturbations. The clinical evaluation of ARF and implications for potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(94 citation statements)
references
References 91 publications
(46 reference statements)
1
87
0
4
Order By: Relevance
“…Traditionally, septic AKI has been thought to be a consequence of a demand and perfusion mismatch, whereby renal blood flow was decreased in the midst of higher metabolic demand [89,90]. Nevertheless, in spite of conflicting animal studies, Langenberg et al [91] reported only 3 studies in humans that have directly calculated renal blood flow in septic AKI via invasive measurements.…”
Section: Endotoxin Effects On Renal Functionmentioning
confidence: 99%
“…Traditionally, septic AKI has been thought to be a consequence of a demand and perfusion mismatch, whereby renal blood flow was decreased in the midst of higher metabolic demand [89,90]. Nevertheless, in spite of conflicting animal studies, Langenberg et al [91] reported only 3 studies in humans that have directly calculated renal blood flow in septic AKI via invasive measurements.…”
Section: Endotoxin Effects On Renal Functionmentioning
confidence: 99%
“…Acute kidney injury (AKI) affects 20 to 50% of intensive care unit (ICU) patients, and it is associated with high mortality, increased ICU length of stay and greater hospitalization cost [1][2][3][4][5]. When renal replacement therapy (RRT) is used, mortality rates can reach up to 80% [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Der reduzierte Blutfluss wurde lange als das Kennzeichen des renalen ANV angesehen, weshalb man es als "Vasomotor Nephropathie" bezeichnete [12]. Die Reduktion des Blutflusses beruht auf einer verminderten Bildung und Wirkung von vasodilatatorischen Substanzen [13] und einem Verlust der renalen Autoregulation [14], was eine persistierende Vasokonstriktion auslöst. Zusätzlich sind die Gefäße sensitiver für vasokonstriktorische Stimuli, was zu einer überproportionalen Vasokonstriktion führt [15].…”
Section: Reduzierter Renaler Blutflussunclassified
“…Zusätzlich sind die Gefäße sensitiver für vasokonstriktorische Stimuli, was zu einer überproportionalen Vasokonstriktion führt [15]. Obwohl der reduzierte renale Blutfluss unweigerlich zu einer Abnahme der GFR führt, ist dies nicht der einzige Grund für den Verlust der GFR und der renalen Schädigung [13,16]. Von größerer Bedeutung scheinen die regionalen Unterschiede in der Nierendurchblutung zu sein akutes Nierenversagen [17]: So ist der Blutfluss besonders in der äußeren Medulla kritisch reduziert [18].…”
Section: Reduzierter Renaler Blutflussunclassified